Normal values for the different classes of venous blood mononuclear cells defined by monoclonal antibodies. Issue 1 (January 1985) - Goff, L K; Habeshaw, J A; Rose, M L; Gracie, J A; Gregory, W
Abstract : We present the data obtained from routine quantitation of normal venous blood mononuclear cells using 19 monoclonal antibodies against defined mononuclear cell surface antigens. The results indicate different values for percentage and absolute numbers of T lymphocytes and of T lymphocyte subsets depending on the monoclonal antibodies used to quantify these populations. In most instances the total number of identified cells was significantly less than the total number of recovered blood mononuclear cells, which suggests the existence in blood of a null cell population. Evidence is advanced to support previous observations that at least a proportion of this population is of B cell lineage, expressing cytoplasmic immunoglobulin but lacking other class or lineage specific markers. The value of a diverse monoclonal panel in routine quantitation of peripheral blood mononuclear cells is discussed.